PRESENCE AND RESIDENCE OF NEAR EASTERNERS IN CRETE DURING THE IRON AGE - Muñoz Sogas, Judith (PEOPLE: International Journal of Social Sciences, 2018)
Since Prehistory, human beings have migrated from one place to another in order to meet their needs. The Iron Age saw an increase of interactions in the Mediterranean Sea. Archaeological settlements of the island of Crete (Greece), such as Knossos, Eleutherna or the Idaean Cave, have provided Near Eastern material that suggests these contacts. The finds indicate the presence of Near Easterners in the island (figurines of Egyptian gods from Knossos show the transmission of oriental religion; North Syrian ivory furniture found at the Idaean Cave and oriental bronzes manufactured at Eleutherna imply a Near Easter craftsmen working there), but also their residence (attested by “cippi”, an oriental mortuary practice). Therefore, between the 9th and the 8th centuries BC, Crete saw some Near Eastern traders and metalworkers who arrived, settled, practised their craft and taught their techniques to local people in the island. This multi-cultural character of Crete shows an early phase of migratory movements where cultural practices are shared among different groups of people It is a phenomenon that implies processes of hybridisation, localisation and even globalisation, reminding us that cultures should never be considered in isolation.